Pengaruh Pembelajaran Berdiferensiasi Dengan Pendekatan Realistic Mathematics Education (RME) Untuk Meningkatkan Hasil Belajar Matematika Siswa - Cahyanti, Nurim Dwi; Erdiana, Lita; Nurhayati, Eni (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
This research aims to determine the effect of differentiated learning with the RME approach on mathematics learning and to determine the results of mathematics learning using differentiated learning with the RME approach in grade 1 students at Pucanganom State Elementary School. This type of research is quantitative research using a Quasi-Experimental Design type experimental method. The subjects in this research were class 1 students consisting of 20 students in class 1 A as the experimental class and 20 students in class 1 B as the control class. In this study, observation sheets, initial tests (pretest) and final tests (posttest) were used. The statistical data obtained were normality tests, homogeneity tests and partial tests which were processed using the SPSS 25.00 program. Based on the results of the partial test, a significance value (2-tailed) was obtained of 0.000 <0.05. So it can be concluded that the research results show that there is an influence on the application of differentiated learning with the RME approach to improve the mathematics learning outcomes of grade 1 students at Pucanganom State Elementary School.